Analysis of the Impact of the Peatland Moratorium on Poverty: Evidence from a Difference-in-Differences Analysis - Zamaya, Yelly; Pratiwi, Sulistya Rini; Purnamasari, Vidya; Susilo, Ignatia Bintang Filia Dei; Abdurakhman, Abdurakhman (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines whether Indonesia's peatland moratorium policy influenced poverty outcomes in Riau Province. Enacted through Presidential Instruction No. 10/2011, the moratorium suspended the issuance of new land-use permits in primary forests and peatland areas as part of the government's commitment to environmental conservation. Using a quasi-experimental Difference-in-Differences (DiD) framework, the study designates districts with peatland coverage exceeding 100,000 hectares as the treatment group, while districts below this threshold serve as the control group. The analysis spans both the pre-moratorium period (2009–2011) and the post-moratorium period (2012–2024). The DiD coefficient of −2.407 (p = 0.228) reveals no statistically significant divergence in poverty trajectories between treated and control areas, indicating that the moratorium lacked direct, measurable effects on household welfare. This outcome underscores the inherent limitations of single-sector environmental governance in resolving the multidimensional character of poverty. Among all covariates examined, educational attainment measured as average years of schooling emerges as the most powerful determinant of poverty reduction (β = −2.468, p < 0.001). Unemployment exhibits a positive association with poverty approaching conventional significance thresholds (β = 0.444, p = 0.053), while GDP per capita shows a statistically significant negative effect. Economic growth, though directionally consistent with poverty reduction theory, does not reach significance, suggesting structural impediments to inclusive growth in the province. These findings call for complementary socioeconomic policies that address human capital deficits and labor market constraints alongside environmental conservation measures.